TINJAUAN EKONOMI SYARIAH TERHADAP JUAL BELI MURABAHAH PADA PERBANKAN SYARIAH - Razali Razali (Faculty of Islamic Economics and Business, IAIN Lhokseumawe, 2017)
Sale and purchase murabahah is a sale and purchase with the price of origin and plus the benefits agreed by both parties sellers and buyers. Sale and purchase murabaha this part of muamalah which is often diparaktikkan in syariah banking in Indonesia. The problem to be studied is how is the sharia economic review of the sale and purchase of murabahah and whether the sale of murabahah in Islamic Banking has fulfilled the provisions of sharia economy. The goal is to find out how the sharia economic review of the sale and purchase of murabahah and whether the practice of buying and selling murabahah in Islamic Banking has appropriate sharia economy. To answer this problem the authors use the type of research field research with qualitative research forms with data collection in the field then processed and analyzed with descriptive analysis then presented to answer the above problems. In addition, data collection from the field is then analyzed and grouped into primary and secondary data. The primary data is data that comes from the field of observation and interview. While the secondary data in the form of bibliographic data which includes books, other supporting books related to the issues being discussed. The results showed that the sharia economic review of the sale and purchase of murabahah in sharia banking is not fully implemented in banking in accordance with the principles of sharia economy. Keyword: Sale and Purchase Murabahah